2011
DOI: 10.4028/www.scientific.net/amr.236-238.225
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Capability of Activated Carbons with High Specific Surface Area by Microbial Enzymatic and Chemical Activation

Abstract: High surface area activated carbon was prepared from waste tobacco after extracting nicotine with microbial enzymatic and chemical activation. Surface properties of the prepared carbons were performed using nitrogen adsorption, and the adsorption behavior of the prepared carbons under different operation conditions on methyl orange was investigated by a batch adsorption experiment. The experimental results show that: using waste tobacco 5.0035g and white- rot fungi volume is 2.0ml, under the conditions of enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Studies show that AC produced from hemp fiber derivatives may present larger surface areas and lower production costs compared to other lignocellulosic materials (Dizbay-Onat et al, 2018;Hossain et al, 2018). In addition, other studies have shown that fungi grow exclusively on hemp fibers (Siwulski et al, 2010), which is a promising alternative method to increase the surface area of AC (Wang et al, 2011;Wang et al, 2019).…”
Section: Experimental Acute Anti-inflammatory Activity Of Preparation...mentioning
confidence: 99%
“…Studies show that AC produced from hemp fiber derivatives may present larger surface areas and lower production costs compared to other lignocellulosic materials (Dizbay-Onat et al, 2018;Hossain et al, 2018). In addition, other studies have shown that fungi grow exclusively on hemp fibers (Siwulski et al, 2010), which is a promising alternative method to increase the surface area of AC (Wang et al, 2011;Wang et al, 2019).…”
Section: Experimental Acute Anti-inflammatory Activity Of Preparation...mentioning
confidence: 99%